Internalisasi Nilai-Nilai Islami Dalam Pendidikan Karakter Di Era Disrupsi Digital - Syamsul Hadi Untung; Moh Isom Muddin; Aqdi Rofiq Asnawi; Farales Sindy; Lutfiatul Khasanah (Jurnal Pendidikan Agama Islam, 2025)
The era of digital disruption poses serious challenges for the world of education, particularly in shaping the character of students based on Islamic values. This study aims to analyze strategies for internalizing Islamic values in character education, with an emphasis on curriculum integration, the use of Islamic technology, role models (uswah hasanah), and the habit of religious activities. The research uses a qualitative approach with a literature study from various primary and secondary sources, including relevant empirical research results. The results of the study show that, first, the integration of Islamic values into all subjects has been proven to be able to foster students' spiritual awareness without being instructional in nature. Second, the use of Islamic technology and Sharia-based digital literacy can be effective means of increasing learning motivation while instilling ethical awareness, with teacher competence being a key factor for success. Third, the example set by teachers and parents (uswah hasanah) is an important strategy in fostering Islamic character, in line with social learning theory which emphasizes the role of behavioral models. Fourth, the habit of religious activities such as congregational prayers, tadarus, and other spiritual activities serve as a moral filter that protects students from the negative influences of digital information. Thus, the strategy of internalizing Islamic values in character education must be carried out comprehensively through